Transportation Policy Financing in Europe - Igor MAYBUROV; Yulia LEONTYEVA (Communications of International Proceedings, 2020)
Analysis of the choices that European states made regarding their transportation policies brings us some important insights. A major achievement of these policies was the creation of a comfortable environment for living and tourism. The aim of this article is to study the trends in the development of transportation policies and financing in Western European countries in the second half of the twentieth century. Our research hypothesis is that the system of transport taxes and charges in Western Europe evolved for a long time and was largely determined by the priorities in these countries' transportation policies. This study relies on methods of historical research and logical analysis. We analyzed transport policies in Western Europe in historical perspective starting from the 1950s. The article discusses the fiscal processes for the implementation of transport policy in the countries of the European Union: Increasing fiscal significance of road charges and taxes, Growing importance of parking pricing, Use of fuel and road taxes as revenue-raising mechanisms. European experience provides important lessons to learn from in terms of transport policy instruments, which can be used to regulate the demand for personal vehicles and public transport. European countries have managed to develop effective strategies for reducing car dependency and increasing the flexibility and scope of their public transport offers.
Keywords: Transport Policy; Financing; Road Charges; Road Taxes; Parking Pricing.